Optimizing Signal and Power Integrity in High-Speed Digital Systems - Venudhar Rao Hajari; Abhishek Pandurang Benke; Shalu Jain; Anshika Aggarwal; Ujjawal Jain (Innovative Research Thoughts, 2024)
High-speed digital systems depend on signal and power integrity for performance, dependability, and usefulness. As digital systems evolve, frequency and data rates rise, making signal integrity and power stability difficult. This study examines advanced methods, tools, and approaches for signal and power integrity optimization in high-speed digital systems. Signal integrity maintains signal quality across the system. Signal distortion, attenuation, and crosstalk may decrease performance and cause data mistakes in high-speed digital systems. The study explores impedance matching, signal conditioning, and layout optimization to address these difficulties. Matching the signal's impedance to the transmission line reduces reflections and signal loss. Equalization and amplification reduce attenuation and distortion to improve signal quality. Strategic component placement and trace routing decrease interference and optimize signal routes in layout optimization. However, power integrity ensures a reliable and clean power supply to all system components. Power noise and oscillations may degrade high-speed digital systems. The study discusses power delivery network (PDN) architecture, decoupling capacitors, and power distribution control to improve power integrity. Effective PDN design requires a low-impedance power supply channel and enough grounding to reduce noise. Power supply stabilization and high-frequency noise filtering depend on decoupling capacitors. Power distribution management requires route design and thermal impacts to ensure power stability.